A 1.5-Year Longitudinal Study of Social Activity in Patients With Schizophrenia - Ohi, Kazutaka; Sumiyoshi, Chika; Fujino, Haruo; Yasuda, Yuka; Yamamori, Hidenaga; Fujimoto, Michiko; Sumiyoshi, Tomiki; Hashimoto, Ryota (Frontiers in Psychiatry, 2019)
Patients with schizophrenia exhibit impairments in their social activity, intelligence quotient (IQ), daily living skills and social function. Social activity is a high-order outcome measure of their lives. Here we attempted to longitudinally evaluate the effects of IQ, daily living skills, social function, psychiatric symptoms and medications on social activity in patients with schizophrenia. The purpose of the current study is to identify the specific factor that affects longitudinal changes in social activity. Sixty-five patients with schizophrenia were assessed at two time points [time 2 (T2, follow-up)-time 1 (T1; baseline)=1.71±0.79 years]. Social activity, IQ, daily living skills and social function were assessed using the Social Activity Assessment (SAA; hrs/week), Short Form of the Wechsler Adult Intelligence Scale (WAIS)-III (WAIS-SF), UCSD Performance-based Skills Assessment (UPSA) and Social Functioning Scale (SFS), respectively. IQ, daily living skills, social function and social activity were significantly improved between T1 and T2 (t=2.0-4.4, p=0.048-3.60×10-5). IQ, daily living skills and social function positively correlated with social activity (lowest p=1.27×10-5), and psychiatric symptoms negatively correlated with social activity over time (lowest p=3.26×10-9). The longitudinal change in social activity was independently and positively correlated with a change in social function (beta=0.35, p=4.63×10-3), particularly interpersonal communication (beta=0.35, p=4.32×10-3). The longitudinal changes in other factors did not directly affect the change in social activity (p>0.05). Based on these findings, social activity is more affected by social function than by other factors.